Zinc (II) complex with a cationic Schiff base ligand: Synthesis, characterization, and biological studies - Lee, S.K.; Tan, K.W.; Ng, S.W.; Ooi, K.K.; Ang, K.P.; Abdah, M.A. (2013)
A cationic Schiff base ligand, TSB (L) and its Zn (II) complex (1) were synthesized and characterized by using CHN, 1H-NMR, FT-IR, UV, LC-MS, and X-ray methods. Their ability to inhibit topoisomerase I, DNA cleavage activities, and cytotoxicity were studied. X-ray diffraction study shows that the mononuclear complex 1 is four coordinated with distorted tetrahedral geometry. The singly deprotonated Schiff base ligand L acts as a bidentate ON-donor ligand. Complexation of L increases the inhibitory strength on topoisomerase I activity. Complex 1 could fully inhibit topoisomerase I activity at 250μM, while L did not show any inhibitory effect on topoisomerase I activity. In addition, L and complex 1 could cleave pBR322 DNA in a concentration and time dependent profile. Surprisingly, L has better DNA cleavage activity than complex 1. The cleavage of DNA by complex 1 is altered in the presence of hydrogen peroxide. Furthermore, L and complex 1 are mildly cytotoxic towards human ovarian cancer A2780 and hepatocellular carcinoma HepG2.